SYNTHESIS AND FIELD TEST OF A PHEROMONE ANALOG OF CHILECOMADIA VALDIVIANA - Heidy Herrera; Wilson Barros-Parada; M. Fernanda Flores; Eduardo Fuentes-Contreras; Jan Bergmann (Journal of the Chilean Chemical Society, 2018)
The main pheromone component of Chilecomadia valdiviana has recently been reported to be (7Z,10Z)-7,10-hexadecadienal. The synthesis of a structural analog, (5Z,8Z)-5,8-tetradecadienyl formate is reported. The pheromone analog was not attractive to male C. valdiviana in the field, nor did it antagonize attraction of males to the pheromone compound.